An ANALYSIS OF SLANG TYPES AND SLANG WORD-FORMATION PROCESSES IN JACK & JACK’S SELECTED SONGS’ LYRICS ON CALIBRASKA ALBUM - Habib , Ichsanul; Panggabean, Christina Innocenti Tumiar; Hidayatullah, Putri (Pro-ELLitera, 2025)
This study aims to find out the types of slang words and the word-formation processes used in Jack & Jack’s selected songs’ lyrics on Calibraska album. The researchers used descriptive qualitative method to analyse the slang types and word-formation process in the selected songs’ lyrics. The findings showed that there are two types of slang found in Jack & Jack’s selected songs in Calibraska album, which are primary slang with 46 words (73%) and secondary slang with 17 words (27%) and there are 6 word-formation processes of the slang words used which are borrowing with 3 words (5.4%), compounding with 4 words (7.8%), blending with 3 words (5.4%), clipping with 37 words (67.3%), conversion with 4 words (7.3%), acronym with 2 words (3.6%), and derivation with 1 word (1.8%). From the data analysis it showed thatprimary slang is the most dominant and clipping is the most dominant in word formation process, which is commonly found in songs.